Applicability assessment of the vickers indentation for determining the fracture toughness of yttria-stabilized zirconia - Vavrukh, Valentyna; Klimczyk, Piotr; Priakhin, Volodymyr; Petryk, Vitalii; Momot, Kinga (Видавництво Львівської політехніки, 2023)
Crack growth resistance of ZrO2-(3-8) mol% Y2O3 ceramics was investigated. Young's modulus by the ultrasonic flaw detection method were determined. Vickers hardness and parameters of cracks after Vickers indentation were obtained. Based on the Young's modulus values, Vickers hardness, and parameters of cracks, the fracture toughness of the investigated ceramics was calculated using 9 different equations of the Vickers indentation method. A comparative analysis of the calculated fracture toughness values with those obtained by the single-edge notch beam method was carried out. It was found that choosing the optimal equation for calculating fracture toughness by the Vickers indentation method is quite difficult and requires comparison with the results of standardized tests. It was shown that to determine crack resistance characteristics of the yttria-stabilized zirconia ceramics, the use of only the Vickers indentation method without comparison with other methods of fracture mechanics is incorrect.
Keywords: YSZ ceramics; Vickers indentation; fracture toughness; Young’s modulus; sintering